Observed and global climate model based changes in wind power potential over the Northern Hemisphere during 1979–2016. (15th January 2019) - Tian, Qun; Huang, Gang; Hu, Kaiming; Niyogi, Dev
Abstract: Using an observed dataset, we study the changes of surface wind speeds from 1979 to 2016 over the Northern Hemisphere and their impacts on wind power potential. The results show that surface wind speeds were decreasing in the past four decades over most regions in the Northern Hemisphere, including North America, Europe and Asia. In conjunction with decreasing surface wind speeds, the wind power potential at the typical height of a commercial wind turbine was also declining over the past decades for most regions in the Northern Hemisphere. Approximately 30%, 50% and 80% of the stations lost over 30% of the wind power potential since 1979 in North America, Europe and Asia, respectively. In addition, the evaluation of climate models shows their relatively poor ability to simulate long-term temporal trends of surface winds, indicating the need for enhancing the process that can improve the reliability of climate models for wind energy assessments. Highlights: Widespread decrease in surface winds is found over the Northern Hemisphere. Wind energy resources are in rapid decline in many places. Climate models' ability in simulating winds and wind energy need to be enhanced.